Laparoscopic and endoscopic cooperative surgery for early gastric cancer: Perspective for actual practice - Zhao, Peng-yue; Ma, Zhao-fu; Jiao, Ya-nan; Yan, Yang; Li, Song-yan; Du, Xiao-hui (Frontiers in Oncology, 2022)
Early gastric cancer (EGC) has a desirable prognosis compared with advanced gastric cancer (AGC). The surgical concept of EGC has altered from simply emphasizing radical resection to both radical resection and functional preservation. As the mainstream surgical methods for EGC, both endoscopic resection and laparoscopic resection have certain inherent limitations, while the advent of laparoscopic and endoscopic cooperative surgery (LECS) has overcome these limitations to a considerable extent. LECS not only expands the surgical indications for endoscopic resection, but greatly improves the quality of life (QOL) in EGC patients. This minireview elaborates on the research status of LECS for EGC, from the conception and development of LECS, to the tentative application of LECS in animal experiments, then to case reports and retrospective clinical studies. Finally, the challenges and prospects of LECS in the field of EGC are prospected and expounded, hoping to provide some reference for relevant researchers. With the in-depth understanding of minimally invasive technology, LECS remains a promising option in the management of EGC. Carrying out more multicenter prospective clinical research related to LECS and EGC is the top priority of promoting the development of this field in the future.